Analisis Dampak Kualitas Layanan Pada Fakultas Ekonomi Universitas di Provinsi Jawa Timur, Jawa Barat dan Jawa Tengah - Hanafi, Imam; Trisolvena, Muhammad Nana; Caroline; Sumiati, Siti (Jurnal EMT KITA, 2023)
This study analyzes the impact of service quality at the Faculty of Economics of several universities in the provinces of East Java, West Java, and Central Java. This study aims to evaluate the correspondence between expectations and reality of 100 students from different Economics Faculties in 3 research provinces using the Convenience Sampling method. Research results show that there is a significant difference between expectations and reality in terms of reliability, showing that service quality at economics faculties in three provinces has still not met students' expectations. A similar phenomenon occurs in relation to the responsiveness factor, highlighting the need to increase the level of service responsiveness. The analysis also highlighted the need to improve trust and empathy elements in services, with significant discrepancies between expectations and reality. T-test results confirm that service quality, especially in the aspects of reliability, responsiveness, trustworthiness, empathy, and tangibility, still does not fully meet students' expectations. Faculty of Economics of three provinces. Therefore, relevant universities should increase efforts to improve the aspects of reliability, responsiveness, trustworthiness, empathy, and tangibility so that students can have more confidence in the services are provided. It is hoped that this step will have a positive impact in enhancing student satisfaction and their academic success.